Types of Oral Questions Used by Teachers in Mathematical Problem Solving Teaching in Primary School Mathematics Teaching - Mahmud, Muhammad Sofwan; Yunus, Aida Suraya Md.; Yunus, Aida Suraya Md.; Sulaiman, Tajularipin (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the types of oral questions commonly used by primary school mathematics teachers in their teaching. Data from the qualitative case study was collected through semi-structured interviews, document analysis and field notes. Six mathematics teachers from six different primary schools were selected as participants of the study using purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained. The study found that, in implementing teaching of mathematical problem solving, four types of oral questions are often used by teachers to guide students’ understanding of mathematical problems. The findings showed that mathematics teachers used text-based questions, multi-mode questions, operational comprehension questions and question- based operation. As a conclusion, the results of the study revealed the importance of oral questioning in the teaching of mathematical problem solving. By using all types of questions identified, students were actually stimulated to understand the mathematical problem and were helped to plan various strategic ways to solve the given mathematical problem.